Detection of Porcine Adulteration in Cosmetic Cream Formulation via TaqMan Probe Real-Time Polymerase Chain Reaction. - S Abd-Gani, S; Mustafa, S; N Mohd Desa, M; F Khairil Mokhtar, N; K Hanapi, U; Zakaria, Z; Yahaya, N; M A Wan Sulaiman, W (International Journal of Engineering and Technology, 2019)
The identification ofÂ lard adulterated in cosmetic cream using TaqMan probe real-time Polymerase Chain Reaction was developed in this research. The laboratory prepared cream was formulated with oil in water (o/w) emulsion with the adulteration of 1%, 3% and 5% of lard (w/w). The total DNA from lard-adulterated cosmetic cream was successfully extracted. The detection assay targeting different gene; universal 18S rRNA and porcine-specific multiple porcine repetitive element (MPRE) which employed with the TaqMan probe. This study targeting 187 bp of amplicons for 18S rRNA while 99 bp of amplicons for Porcine-specific probes. A comparison of quantification cycle (Cq) with prior to percentage of adulteration were detected. Lard-adulterated cream was amplified for 18S rRNA while no detection was detected for Porcine-specific probes. The Cq value obtained might be vary as proposed by the hypothesis depending on the total recovery of extracted DNA from the lard-adulterated cream.Â Â